Custody and Obligations of Parental Alimation of Children After the Breakup of Marriage Due to Divorce in Terms of Law Number 1 Of 1974 Concerning Marriage - Hamonangan, Sobardo (Faculty of Law, Universitas Pekalongan, 2024)
The research entitled;Parents' Custody Rights and Alimentary Obligations for Children After Dissolution of Marriage Due to Divorce in View of Law Number 1 of 1974 concerning Marriage; was carried out in the jurisdiction of Jayapura City with the aim of finding out and analyzing the causal factors the occurrence of divorce and custody and fulfillment of parental alimony obligations towards children.This research is empirical legal research using the Normative Juridical and Empirical Juridical approach methods. The Normative Juridical Approach is by reviewing the provisions of statutory regulations relating to the rights aspect of divorce and the legal consequences of divorce in relation to Custody Rights and Parental Alimony obligations following the dissolution of the marriage due to divorce, while the Empirical Juridical approach is by looking at the implementation of the provisions Laws relating to divorce and custody rights and parental alimony obligations apply in society. The results showed that the factors causing divorce in the city of Jayapura in general for the continuous disputes, disputes and quarrels triggered by the attitudes and behavior of both the husband and wife namely a. The existence of love with women and other men, b. Husband rarely goes home; c. Husband is light hand by beating the wife. Meanwhile, in most court decisions on divorce cases, the majority of judges decide that custody rights are given to the wife based on psychological considerations and legal considerations. The psychological considerations are because the children are still small and not yet mumayyiz so they still really need more attention from their mother, and the husband's morals are not good, so there are concerns that it will affect the child's psychological development during his growth period. Furthermore, regarding the fulfillment of alimony obligations in the context of the care and development of the child, in general it is not carried out well, generally parents (fathers) lack or neglect their alimony obligations towards the child on the grounds that they have a new family, because they are not given custody, because of their economic capabilities, so does not carry out his alimony obligations as ordered by the applicable statutory provisions.